'Another tool in my toolbox': Training school teaching assistants to use dynamic temporal and tactile cueing with children with childhood apraxia of speech. (October 2019) - Lim, Jacqueline; McCabe, Patricia; Purcell, Alison
This study explored the feasibility of training school teaching assistants to provide the treatment, Dynamic Temporal and Tactile Cueing to treat childhood apraxia of speech (CAS, also known as developmental verbal dyspraxia). The study used a single case experimental design across behaviours and a qualitative evaluation of teaching assistant experiences using interviews. Two student-teaching assistant dyads participated. One child was aged 6;2 (6 years 2 months) and the other 5;6 at the time of the study. Both participants had speech characteristics consistent with the features outlined in the 2007 Technical Report on CAS from the American Speech and Language Hearing Association (ASHA). These included lengthened and disrupted coarticulatory transitions between sounds and syllables, inappropriate prosody and inconsistent errors on consonants and vowels. Treatment outcomes were measured using visual analysis and calculations of total-change improvement rate difference (TC-IRD) and composite IRD (C-IRD) based on percent of phonemes correct. Fidelity to the treatment protocol was measured using a Fidelity Score. Visual analysis of both child participant's data showed an upward trend for all treatment and similar words and a flatter trajectory for control words. Both child participants had a TC-IRD score of 100% for all treatment words. One child also had a TC-IRD score of 100% for their similar words and a TC-score of 25% for their control words. The second child had a TC-score of 67% for similar and control words. Both teaching assistants had a Fidelity Score of over 90%. Both teaching assistants reported positive experiences in conducting the program. Training teaching assistants may be an effective means of providing treatment to children with CAS while they are at school. Training teaching assistants also helps to improve their capacity which may have positive implications in their interactions with other children with speech sound disorders.